Symplasmic phloem loading and subcellular transport in storage roots are key factors for carbon allocation in cassava - Rüscher, David; Vasina, Viktoriya V.; Knoblauch, Jan; Bellin, Leo; Pommerrenig, Benjamin; Alseekh, Saleh; Fernie, Alisdair R.; Neuhaus, H. Ekkehard; Knoblauch, Michael; Sonnewald, Uwe; Zierer, Wolfgang (Plant Physiology, 2024)
Cassava (Manihot esculenta) is a deciduous woody perennial shrub that stores large amounts of carbon and water in its storage roots. Previous studies have shown that assimilating unloading into storage roots happens symplasmically once secondary anatomy is established. However, mechanisms controlling phloem loading and overall carbon partitioning to different cassava tissues remain unclear. Here, we used a combination of histological, transcriptional, and biochemical analyses on different cassava tissues and at different timepoints to better understand source–sink carbon allocation. We found that cassava likely utilizes a predominantly passive symplasmic phloem loading strategy, indicated by the lack of expression of genes coding for key players of sucrose transport, the existence of branched plasmodesmata in the companion cell/bundle sheath interface of minor leaf veins, and very high leaf sucrose concentrations. Furthermore, we showed that tissue-specific changes in anatomy and non-structural carbohydrate contents are associated with tissue-specific modification in gene expression for sucrose cleavage/synthesis, as well as subcellular compartmentalization of sugars. Overall, our data suggest that carbon allocation during storage root filling is mostly facilitated symplasmically and is likely mostly regulated by local tissue demand and subcellular compartmentalization.
CRIS-Team Scopus Importer:2024-10-11